An Analysis of Students’ English Speaking Skill at Coastal Schools of Bengkulu City, Indonesia - Ildi - Kurniawan; Syafrizal Sabaruddin; Fernandita Gusweni J (English Department - University of Sultan Ageng Tirtayasa, 2018)
This research was not only aimed at describing students’ speaking skill in English especially in coastal areas of Bengkulu city, Indonesia, but also investigati g the factors which influenced the skills. Mixed method (qualitative and quantitive) approach was used in this research. Meanwhile, the subjects of the research were 159 students (males and females) in total, coming from three different schools. The data were obtained through recording by using camera, handycam and also by administering a questionnaire. The collected data were then analyzed by using Interactive Model namely; data reduction, data display, and drawing a conclusion. The findings showed that the students’ speaking skill in English was in moderate category in which grammar, vocabulary and fluency became main problems for them in studying English speaking skill. In addition, lack of practice and confidence were believed positively to be the trigger for those problems.